Renovação Carismática Católica na perspectiva do outro: um olhar de fora para dentro - Toscano, Roque (2001)
Even though the decline of religion was announced by rationalism, the characteristic mark of modernism, it was in fact the absent phenomenon at the turn of the century. Contrary to expectations, there has been an awakening to the Sacred in the form of a veritable explosion of religious movements on a world scale. Such movements sprung up with their own particular characteristics, which fit into what many authors have already called postmodernism. In their composition, these movements include an attempt to recover the emotional dimension of the human being. In the symbolic field of Christian devotion, these movements are called Pentecostal. In the narrower field of Roman Catholic Christianity, they have been given the generic title of Charismatic Renewal. This religious movement, based on the action of the Holy Spirit, has always existed, as witnessed in the Acts of the Apostles and the First Epistle to the Corinthians. For this reason, this new flowering has been given the name of revivalist movements. Weber speaks of charism, which in Christianity is seen as a gift of the Spirit, as something contrary to the hierarchical institution. Although this notion should be discussed and deepened somewhat more, historically, it cannot be denied that there has been a certain aversion towards the Charismatic experience on the part of the hierarchy of the Catholic Church. Naturally, from this apparent incompatibility tensions arise, which in the religious field could bring a new dynamism into the religious praxis of these movements. This work, with field and bibliographical research data, sets out to identify today s image of the Charismatic Renewal from the viewpoint of those who do not belong to this religious field be they practicing Catholics or scientists of religion.